Natural antibiotic nutrient solution fertilizer composition containing wet crushed fermented product of insect larvae - KIM, JONG JU (2023)
The present invention relates to a nutrient solution fertilizer composition comprising an EM ferment of the wet pulverized remains of caterpillars of the same species, wherein the raw materials of the ferment can be further added to the raw materials of the ferment, such as clotted blood from slaughtered cows and pigs, sea quirt husk, Sargassum horneri, Lespedeza cuneata, Paulownia coreana leaves, Glycine max, Styrax japonicus, and Phytolacca acinosa. The ferment of the present invention of the present invention has excellent growth enhancement effect in plant cultivation, and the present invention can be used to easily prepare nutrient solution fertilizer for hydroponic cultivation of various fruits and vegetables, leafy vegetables, etc. 본 발명은 동애등에 유충의 습식분쇄물의 EM 발효물을 함유하는 양액 비료 조성물에 관한 것으로서, 상기 발효물의 원료에 선지, 멍게껍질, 괭생이모자반, 야관문, 오동나무 잎, 대두박, 때죽나무, 자리공 등이 더 추가될 수 있다. 본 발명의 발효물은 식물 재배시 생육증진효능이 우수하여, 본 발명을 통해 다양한 과채류, 엽채류 등의 수경재배용 양액 비료를 용이하게 제조할 수 있다.